Investigation of Electrostatic Interactions towards Controlling Silylation‐Based Kinetic Resolutions. Issue 30 (28th July 2019) - Zhang, Tian; Redden, Brandon K.; Wiskur, Sheryl L.
Abstract : Electrostatic interactions between a silylated isothiourea intermediate and an ester π system were explored by determining how variations in sterics and electronics affect the selectivity of a silylation‐based kinetic resolution. Sterics on the π systems affect the selectivity factors of alkyl 2‐hydroxycyclohexanecarboxylates, resulting in a strong correlation of selectivity factors to Charton values. Induction effects of electron‐withdrawing substituents on phenyl esters significantly enhance selectivity supporting an edge to face π–π interaction. The linear free energy relationships that were uncovered will aid in future incorporation of intermolecular electrostatic interactions towards controlling asymmetric reactions. Abstract : The intermolecular interactions that aid in controlling asymmetric reactions are investigated. Alterations in the electronics and sterics of a π system are studied to understand the effect on selectivity that results from electrostatic interactions between the catalyst and the substrate.